The Influence of Word of Mouth and the Use of Instagram Social Media on Tourism Demand at Viral Tanjung Karang Beach - Jastian Wahyuda Prayoga; Diswandi Diswandi (West Science Social and Humanities Studies, 2024)
The purpose of this research is to investigate the impact that social media platforms like Instagram and word-of-mouth advertisements have on the demand for tourism at the popular Tanjung Karang Beach. The methodology that was utilized was quantitative research, and the data collecting procedures were carried out by means of the distribution of Google form questionnaires to 97 individuals who participated in the study. A favorable and significant effect on tourism demand is indicated by the findings of this study, which imply that word of mouth has an effect. The utilization of social media platforms such as Instagram has a favorable and considerable impact on the demand for travel. While the use of social media platforms like Instagram and word-of-mouth have a good and significant impact on tourism demand, the influence of word of mouth is also a key factor.